A novel analytical method for sensitive determination of lead: Hydrogen assisted T-shape slotted quartz tube-atom trap-flame atomic absorption spectrometry - Uslu, Humeysa; Buyukpinar, Cagdas; Unutkan, Tugce; Serbest, Hakan; San, Nevin; Turak, Fatma; Bakirdere, Sezgin (ELSEVIER SCIENCE BV, 2018)
Lead is a toxic metal which affects human health badly due to its high toxicity. The wide application range of lead causes environmental contamination of air, water and soil. Flame atomic absorption spectrometry is one of the simple and economical instrument used for the determination of heavy metals, but it has low sensitivity due to low sample introduction efficiency. In this study, a sensitive analytical method was developed by using T-shaped slotted quartz tube as an atom trap unit to get lower detection limit for lead. The trapped atoms were released using hydrogen gas which supplies reducing environment in T-SQT-AT-FAAS system. Factors such as trapping period, sample and fuel flow rates were optimized to obtain high sensitivity. Under the optimum conditions, limits of detection and quantitation were found to be 0.6 and 2.1 mu g L-1, respectively. Accuracy of the developed method was checked and results found under the optimum conditions agreed with the certified value of coal fly ash standard reference material. The developed method was applied to water samples to figure out its suitability. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Lead; FAAS; T-SQT; Atom trap; Hydrogen; VAPOR GENERATION; HEALTH-RISK; CADMIUM; WATER; PB; PRECONCENTRATION; EXPOSURE; DISEASE; SAMPLES; BURDEN; Chemistry